Chinese businesses and transnational knowledge transfer under constrained environment: results from the field in Ghana. (3rd January 2021) - Ameyaw-Brobbey, Thomas; Gupta, Urmi
China's recent economic success has deepened its engagement with Africa offering a platform for its experience of development and achievement to be transferred to or copied by Africans. What exactly are Chinese businesses teaching Ghanaian workers? What constraints impede the knowledge transfer and the learning process? This article's findings are based primarily on the results of a field study conducted in Ghana between March and July 2019 on 26 Chinese firms, involving 360 Ghanaian workers. It employed a mixed research method of questionnaires and informal interviews to collect data. Using content analysis and IBM SPSS Statistics Version 23, the study found that although grievances exist on salary, job security, safety concerns and others, Ghanaian workers generally acknowledge significant transfer and knowledge learning from Chinese firms and employers which they believe would not only enhance their personal development but a source of impetus for Ghana's development.